PENGARUH LATIHAN PASSING BAWAH BERPASANGAN TERHADAP KEMAMPUAN PASSING BAWAH PADA TIM BOLA VOLI SMPN 06 SIAK HULU - Ordones, Ronaldo; ', Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Issues raised in this research is that the passing skills down yet so good. This is evident from some of the matches have been followed as the match between the level of schools in Pekanbaru, as well as in the match National Student Sports Olympiad (O2SN) secondary school level first to be held each year. Volleyball team SMPN 06 Siak Hulu at the time of passing down not so optimal, such as the passing was not until to teammate, the ball does not go up while doing passing under and movement rudimentary when making passing below. This research is a research with experimental treatment (Experimental), the population in this study is SMPN 06 Siak Hulu. Sample in this study is a population which numbered 12 people. The technique can capture data from the pre-test and post-test. The instruments used in this research is to test passing down with a rope, which aims to measure the ability of passing down. As the independent variable is the practice of cou[le down passing (X), while the dependent variable is below the passing ability (Y). After that, the data is processed with statistical, normality test with Liliefors test at significant level 0,05α. The hypothesis is the effect of couple down passing drills toward passing down skills. Based on t test analysis produces Thitung of 5,36 and 1.796 Ttabel means Thitung> Ttabel. It can be concluded that Ha is accepted, it concludes that there is significant influence from couple down passing of the ability of passing down the volleyball team SMPN 06 Siak Hulu. Key Words :  Couple down passing drills, down passing, volleyball